IMMU-18. FAVORABLE OUTCOME IN REPLICATION REPAIR DEFICIENT HYPERMUTANT BRAIN TUMORS TO IMMUNE CHECKPOINT INHIBITION: AN INTERNATIONAL RRD CONSORTIUM REGISTRY STUDY. (4th December 2020) - Bouffet, Eric; Sudhaman, Sumedha; Chung, Jiil; Kelly, Jacalyn; Coblentz, Ailish; Edwards, Melissa; Lipman, Tatiana; Zhang, Cindy; Ercan, Ayse Bahar; Sambira, Lauren; Bendel, Anne; Bielack, Stefan; et al.
Abstract: Pediatric brain tumors with replication repair deficiency (RRD) are hypermutant and may respond to immune checkpoint inhibition (ICI). We performed a consortium registry study of ICI in recurrent RRD cancers. Clinical and companion biomarkers were collected longitudinally on all patients. Biomarkers included tumor mutational burden (TMB), neoantigens and genetic signatures obtained from whole genome and exome sequencing. Immune inference was obtained by RNAseq and T cell rearrangement was collected in the tumor and in blood throughout treatment. Of the 46 tumors on the study, 32 were brain tumors with glioblastoma in 96%. Rapid, objective responses (>50%) were observed in 50% of glioblastomas. Three year overall survival for the whole cohort was 48+/-8% which compares favorably with historical controls. Brain tumors fared worse with OS of 39+/-10% and late recurrences observed even after 2 years of therapy (p=0.02). Tumor size and acute "flare" constitute poor outcome throughout all cancers. While all tumors are hypermutant, TMB and predicted neoantigens correlated with response to ICI (p=0.02). Specific signatures extracted from SNVs and total mutations predicted response to ICI and favorable outcome (p=0.005). RNA inference and TCR reveal that the FLARE phenotype is mostly acute nonspecific immune response and not true progression. Finally, glioblastomas (n=8) which failed single agent ICI had favorable responses to combinational immunotherapies with prolonged survival of 65%+/-8% at one year after failure vs 0 for other patients (p=0.01). RRD glioblastomas exhibit favorable outcome and responses to ICI. Combinational therapies based on tumor and immune signatures of these cancers are necessary.